L-cysteine ethyl ester prevents and reverses acquired physical dependence on morphine in male Sprague Dawley rats - Bates, James N.; Getsy, Paulina M.; Coffee, Gregory A.; Baby, Santhosh M.; MacFarlane, Peter M.; Hsieh, Yee-Hsee; Knauss, Zackery T.; Bubier, Jason A.; Mueller, Devin; Lewis, Stephen J. (Frontiers in Pharmacology, 2023)
The molecular mechanisms underlying the acquisition of addiction/dependence to morphine may result from the ability of the opioid to diminish the transport of L-cysteine into neurons via inhibition of excitatory amino acid transporter 3 (EAA3). The objective of this study was to determine whether co-administration of the cell-penetrant L-thiol ester, L-cysteine ethyl ester (L-CYSee), would reduce physical dependence to morphine in male Sprague-Dawley rats. Injection of the opioid-receptor antagonist, naloxone HCl (NLX; 1.5 mg/kg, IP), elicited pronounced withdrawal phenomena in rats which received a subcutaneous depot of morphine (150 mg/kg) for 36h and which were receiving a continuous infusion of saline (20 L/h, IV) via osmotic minipumps for the same 36h period. The withdrawal phenomena included wet-dog shakes, jumping, rearing, forepaw licking, 360 o circling, writhing, apneas, cardiovascular (pressor and tachycardic) responses, hypothermia and body weight loss. NLX elicited substantially reduced withdrawal syndrome in rats that received an infusion of L-CYSee (20.8 μmol/kg/h, IV) for 36h. NLX precipitated a marked withdrawal syndrome in rats that had received subcutaneous depots of morphine (150 mg/kg) for 48h) and a co-infusion of vehicle. However, the NLX-precipitated withdrawal signs were markedly reduced in morphine (150 mg/kg for 48h)-treated rats that began receiving an infusion of L-CYSee (20.8 mol/kg/h, IV) at 36h. In similar studies to those described above, neither L-cysteine nor L-serine ethyl ester (both at 20.8 mol/kg/h, IV) mimicked the effects of L-CYSee. This study demonstrates that L-CYSee attenuates the development of physical dependence to morphine in male rats and reverses dependence acquired prior to administration of L-CYSee, most likely by intracellular actions within the brain. The lack of effect of L-serine ethyl ester (oxygen atom instead of sulfur atom) strongly implicates thiol biochemistry in the efficacy of L-CYSee. Accordingly, L-CYSee and analogues may be a novel class of therapeutics that ameliorate the development of physical dependence to opioids in humans.